Ethical-economic dilemmas in business education - Remišová, Anna; Lašáková, Anna; Búciová, Zuzana (Business, Management and Economics Engineering, 2014)
The main purpose of the article is to support the idea of institutionalizing business ethics education at all business schools. Further, the article stresses the importance of using ethical-economic dilemmas in business ethics education. It argues that business students should learn that managerial work is too complex to make do with expertise and experience and help them to acquire the skill of ethical reflection of economic activity. Solving ethical-economic dilemmas in business ethics courses helps to develop cognitive skills in considering economic or managerial problems on the basis of ethical and economic interaction. In order to support the main purpose stated above, we aimed at getting a picture of how respondents assess and solve an ethical-economic dilemma. Hence, this article presents results of an empirical investigation of the ethical decision-making (EDM) process on a sample of Slovak students of Management.